Why all MODY variants in transcription factor genes are dominantly inherited - Zug, Roman (Frontiers in Genetics, 2025)
Maturity-onset diabetes of the young (MODY) is an autosomal dominant form of monogenic diabetes, frequently caused by heterozygous loss-of-function variants in transcription factor (TF) genes. Why are MODY variants in TF genes dominantly inherited? Here I present a systems biology-based explanation. The fact that MODY-associated TFs are master regulators of pancreatic β cell fate suggests that pathogenic variants cause defects in cell fate determination. From a systems biology perspective, cell fate defects are based on disrupted bistability, a crucial feature of dynamical systems to make binary choices. Bistability requires both positive feedback and ultrasensitivity, the latter often in the form of cooperativity. MODY-associated TFs exhibit both features, which not only allows for bistability, but also makes these TFs extremely dosage sensitive, which explains why heterozygous loss of function is sufficient to cause a disease phenotype. A review of the literature strongly supports this hypothesis. Moreover, the hypothesis also helps to explain why incomplete penetrance is such a pervasive feature of MODY-associated variants in TF genes.